Longitudinal associations between adolescent catch-up sleep, white-matter maturation and internalizing problems - Guldner, Stella; Sarvasmaa, Anna S.; Lemaître, Hervé; Massicotte, Jessica; Vulser, Hélène; Miranda, Ruben; Bézivin-Frere, Pauline; Filippi, Irina; Penttilä, Jani; Banaschewski, Tobias; Barker, Gareth J; Bokde, Arun LW; et al. (Developmental cognitive neuroscience, 2023)
Sleep is an important contributor for neural maturation and emotion regulation during adolescence, with long-term effects on a range of white matter tracts implicated in affective processing in at-risk populations. We investigated the effects of adolescent sleep patterns on longitudinal changes in white matter development and whether this is related to the emergence of emotional (internalizing) problems. Sleep patterns and internalizing problems were assessed using self-report questionnaires in adolescents recruited in the general population followed up from age 14-19 years (N = 111 White matter structure was measured using diffusion tensor imaging (DTI) and estimated using fractional anisotropy (FA). We found that longitudinal increases in time in bed (TIB) on weekends and increases in TIB-variability between weekdays to weekend, were associated with an increase in FA in various interhemispheric and cortico-striatal tracts. Extracted FA values from left superior longitudinal fasciculus mediated the relationship between increases in TIB on weekends and a decrease in internalizing problems. These results imply that while insufficient sleep might have potentially harmful effects on long-term white matter development and internalizing problems, longer sleep duration on weekends (catch-up sleep) might be a natural counteractive and protective strategy.